Functional analysis of the human rib cage over the vital capacity range in standing position using biplanar X-ray imaging. (May 2022) - Vergari, Claudio; Skalli, Wafa; Clavel, Louis; Demuynck, Michel; Valentin, Rémi; Sandoz, Baptiste; Similowski, Thomas; Attali, Valérie
Abstract: Pathologies of the respiratory system can by accompanied by alterations of the biomechanical function of the rib cage, as well as of its morphology and movement. The assessment of such pathologies could benefit from rib cage kinematic analysis during breathing, but this analysis is challenging because of the difficulties in observing and quantifying bone movements in vivo. This work explored the feasibility of using biplanar x-rays to study rib cage modifications at different lung volumes and evaluated the potential of the method to characterize rib cage kinematic patterns in patients. Forty-seven asymptomatic adults and eleven obstructive sleep apnea syndrome (OSAS) patients underwent biplanar x-rays at three lung volumes: normal breathing, maximal and minimal volume. Rib cage and spinopelvic positional parameters were computed from 3D reconstruction of the skeleton. Results showed that inspiration mostly mobilized the ribs and costo-vertebral junction, while expiration was driven by the spine. OSAS patients had a different sagittal profile at rest than asymptomatic subjects, but these differences decreased at maximal and minimal volume. This suggests that patients employed different biomechanical strategies to attain a trunk configuration similar to asymptomatic subjects at minimal and maximal lung volume. This study confirmed that the proposed method could have an impact for the clinical assessment and understanding of pathologies involving breathing function, and which directly affect rib cage morphology. Highlights: Assessing the movement of the rib cage during breathing is still a challenge. Biplanar x-ray was used to measure rib cage morphology at three lung volumes. Different respiratory strategies were deployed by patients and healthy subjects. The proposed method offers a novel approach to functional examination of rib cage.